Assessment of Biogas Plant Firms by Application of Annual Accounts and Financial Data Analysis Approach - Mattia Iotti; Giuseppe Bonazzi (Energies, 2016)
Firms operating biogas plants are often characterized by making significant investments in fixed assets financed by equity and, mainly, financial debt. These firms have experienced significant growth in Italy, partly as a result of public contributions. The objective of the research is to analyze the management of biogas plant firms by analyzing annual accounts as the main document of use to third parties for the evaluation of a firm’s management. The research, conducted on a sample of 22 firms using 110 year-data, has highlighted that economic and financial margins are different, though often statistically correlated. The research shows that profitability and cash generation in the biogas plant industry are high, even if the generation of cash flow is less than the return on equity, and there are firm cases of having difficulty in financial debt repayment, even in the presence of positive economic margins. The research also shows that return on equity greatly exceeds the performance of Italian government bonds and of the majority of industrial sectors; this result points to the significant increase in returns on equity capital in the industry, potentially damaging other sectors, and highlighting the risk of the distortive use of public resources.